7x + 17 = 7x - 17
7x + 17 - 7x = 7x - 17 - 7x
17 = -17
Inconsistent: for no value of x is the above equation true. 17 ≠ -17.
Hope this helps! :)
Answer:
1,850
Step-by-step explanation:
600+.05(25000)=1,850
Answer:
its 45
Step-by-step explanation:
Answer/Step-by-step explanation:
Recall: ![x^{-a} = \frac{1}{x^a}](https://tex.z-dn.net/?f=%20x%5E%7B-a%7D%20%3D%20%5Cfrac%7B1%7D%7Bx%5Ea%7D%20)
a. ![4^{-3} = \frac{1}{4^3} = \frac{1}{64}](https://tex.z-dn.net/?f=%204%5E%7B-3%7D%20%3D%20%5Cfrac%7B1%7D%7B4%5E3%7D%20%3D%20%5Cfrac%7B1%7D%7B64%7D%20)
b. ![13^{-2} = \frac{1}{13^2} = \frac{1}{169}](https://tex.z-dn.net/?f=%2013%5E%7B-2%7D%20%3D%20%5Cfrac%7B1%7D%7B13%5E2%7D%20%3D%20%5Cfrac%7B1%7D%7B169%7D%20)
c. ![(-3)^{-2} = \frac{1}{-3^2} = \frac{1}{9}](https://tex.z-dn.net/?f=%20%28-3%29%5E%7B-2%7D%20%3D%20%5Cfrac%7B1%7D%7B-3%5E2%7D%20%3D%20%5Cfrac%7B1%7D%7B9%7D%20)
Answer:
n-9=13
n=22
Step-by-step explanation: